TECHNOLOGY-BASED SOP DEVELOPMENT FOR TRANSPARENT VILLAGE APPARATUS SELECTION: ADVANCING GOOD GOVERNANCE IN KLAMPOK, MALANG, EAST JAVA, INDONESIA - Mokhammad Nurruddin Zanky; Choirul Anam; Sigit Permansyah (Universitas Negeri Surabaya, 2026)
Phenomenon/Issue: Issues surrounding transparency, efficiency, and professionalism within the recruitment of village officials remain a persistent national challenge, often obstructing the realization of good governance. Such complications typically stem from the absence of Standard Operating Procedure (SOP) and the underutilization of technology in selection processes, which frequently trigger social friction and public skepticism regarding the integrity of election outcomes. Purpose: This study aims to develop a comprehensive SOP and a digital-based selection instrument that incorporates Computer-Based Testing (CBT) into the recruitment framework. Novelty: The primary novelty of this research lies in the integration of Computer-Based Testing (CBT) within a comprehensive digital SOP framework, covering the entire spectrum from registration to the real-time announcement of results Research Methods: This study employs a Research and Development (R&D) design, adopting the systematic developmental phases established by Borg & Gall Results: This research culminates in three distinct outputs: (1) a digital-based SOP for village official selection, (2) a CBT-integrated selection instrument, and (3) Intellectual Property Rights (IPR) certification pertaining to the newly established SOP. Research Contributions: This research contributes to the enrichment of public management literature, particularly regarding digital innovation in the implementation of local governance selection processes.